PENGARUH FAKTOR LINGKUNGAN BISNIS EKSTERNAL DAN PERENCANAAN STRATEGIK TERHADAP KINERJA PERUSAHAAN - Andri Ariansyah Nasution; Anggi Mayasari Lubis; Dini Azlina Pane; Sherlyta Mardiani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to determine the influence of external business environmental factors and strategic planning on company performance. This study was conducted with a sample of 30 respondents with this sampling technique is probability sampling from multiple linear regression calculations, obtained Y = 3.302 + 0.564X1 + 0.661X2 The results of this study obtained t test, for variables: External Business Environment Factors (X1) t count (2.505) > t table (2.051831) with a significant value of 0.000 <0.05, meaning that there is a significant influence of External Business Environmental Factors on Company Performance. Meanwhile, for the results of the t-test of Strategic Planning (X2), namely t count (2.690) > t table (2.051831) with a significant level of 0.000 <0.05, meaning that there is a significant effect of Strategic Planning on Company Performance. Based on the calculated F test of 36,489 > Ftable 3.35, which means that simultaneously or together External Business Environmental Factors (X1) and Strategic Planning (X2) have a significant effect on Company Performance.